Antagonis Bacterial Selection of Siam Patin Larvae (Pangasius hypopthalmus) Toward Aeromonas hydrophila - ARDIANSYAH KURNIAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2011)
Bacterial isolate of Patin siam ( Pangasius hypopthalmus) larvae are Bacillus mycoides, Bacillus megaterium, Micrococcus sp, Acinetobacter baumannii, Pseudomonas putida, and Actinobacillus sp. Bacterial isolate identification on protein precipitation method showed prohibit value is 6,07 – 6,20 mm. Extracellular metabolite method revealed exclude value is 7,16 – 16,14 mm. Actinobacillus sp have ability for proscribe bigger than other bacteria isolate.